PERATURAN DAERAH, ANTARA KEPENTINGAN PEMERINTAH PUSAT DAN PEMERINTAH DAERAH - Supriyadi, Supriyadi (Jurnal Cakrawala Hukum, 2016)
Regional Regulation as one of law regulation product is an instrument for regulating government matters thatinclude in regional autonomy matters. Especially for Municipal or City Law Regulation, regulating authorityis held on Municipal or City House of Representatives and its leader. Normatively, the existence of Municipalor City Regulation is formed to regulate about the providence government business that includes in regionalautonomy, despite from expose the higher law regulation and regulate the unique character of the region thatdepends on law and norms. The enforcement of the legal regulation is expected to be mean to perceive nationalpolicy and government development program in order to reach national goal. Practically, it is not closechances that the legal regulation from regional formed is not relevant to the natiional goal. When that happened,Ministry of Domestic Affair and Governor can directly cancel the irrelevant law regulation unless Constitutional Court cancels that authority, the Central government no longer has authority to cancel it. It has to be doneby an assessment through Judicial Review under Supreme Court. This condition could be an obstacle in development accelerate, especially in economic sector in term of creating business and investment in the regional area.